Establishment of Inclusive Business on Coffee Production in Bali Province: Lesson from the Coffee Development Project in Nusa Tenggara Timur Province, Indonesia - Sedana, Gede; Astawa, Nengah Dasi (Asian Journal of Agriculture and Rural Development, 2019)
Indonesia is one of the biggest coffee producers in the world. However, farmers’ incomes are still relatively small due to low productivity, poor quality, and low price, as well as limited access to information, technology, and market. This study aims to describe the effect of inclusive business on coffee development in Bali, based on the Flores experience. The results of the study pointed out that the experience of inclusive business on coffee development in Nusa Tenggara Timur Province might also be implemented in Bali. The business model established should include the coffee farmers/farmers’ cooperative, coffee buyer/exporter, bank, government, research institution, and independent actors. Among the market actors, they should have mutualism partnership in order to obtain economic incentives. This could ensure the sustainability of inclusive business on coffee development.